Effect of depression and serotonin reuptake inhibitors antidepressant treatment during pregnancy on protein expression in the human placenta: A quantitative proteomics analysis - Linda Ok; Leanne Ohlund; Amy M. Inkster; Kayleigh S. J. Campbell; Maria S. Peñaherrera; Ursula Brain; Lekha Sleno; Wendy P. Robinson; Amadou Barry; Tim F. Oberlander; Cathy Vaillancourt (PLoS ONE, 2025)
Depression is one of the most prevalent mental health disorders affecting pregnant individuals, and serotonin reuptake inhibitors (SRIs) are the most prescribed medications to treat depressive symptoms during pregnancy. Both depression and SRI exposure may have developmental impacts, and as randomizing exposures and non-treatment is not feasible in humans, distinguishing the effect of each factor often remains challenging. To date, much of what guides clinical practice stems from reports of pregnant individuals and fetal/infant outcomes, overlooking the significant role of the placenta in maintaining a healthy pregnancy and mother-fetal health. In this study, we explored the effect of depression and SRI antidepressant treatment during pregnancy on the placental proteome. A shotgun proteomics method with liquid chromatography and tandem mass spectrometry (LC-MS/MS) was performed. A cohort of pregnant individuals (n = 82) was recruited in their 2 nd trimester, and clinician-rated mood symptoms measured using the Hamilton Depression Rating Scale (HAM-D) were obtained from them during pregnancy to identify three exposure groups: non-depressed; depressed/non-SRI-treated; depressed/SRI-treated. Differential protein expression and over-representation analyses on the placentas of the group with depression/non-SRI compared with placentas from healthy individuals showed an increase in antioxidant enzymes and various senescence-associated secretory phenotypes (SASP) as well as a decrease in histone proteins. Such protein expression patterns are potentially indicative of placental senescence. Our findings reveal that depression not treated with SRIs is associated with the upregulation of proteins involved in platelet activation, degranulation, coagulation cascade, and amyloid fiber formation in the placenta. In contrast, when comparing placentas from the depressed group treated with SRIs to those with depressive symptoms without SRI treatment, we observed a downregulation of proteins related to senescence, amyloid fiber formation, and platelet activation in the SRI-treated group. This study suggests that treatment with SRIs may prevent the placental alterations observed in antenatal depression, such as placental senescence, platelet activation, and amyloid fiber formation, and, ultimately, pregnancy and fetal outcomes. Further studies are needed to confirm these findings.